2016
DOI: 10.1161/circep.116.003960
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Significance of the Early Repolarization Pattern in Sudden Arrhythmic Death Syndrome Families

Abstract: Background-The early repolarization (ER) pattern is associated with sudden death and has been shown to be heritable. Its significance when identified in families affected by sudden arrhythmic death syndrome (SADS) remains unclear. Methods and Results-We analyzed 12-lead ECGs of 401 first-degree relatives of individuals who had died from SADS.The prevalence of ER patterns was compared with family-clustered controls. ER was more common in SADS family members than in controls (21% versus 8%; odds ratio: 5.14; 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Studies among first-degree relatives of patients with sudden arrhythmic death syndrome show that ERP is more prevalent in family members than in controls, indicating that ERP is an important potentially inheritable proarrhythmic trait (18,19). Moreover, in family studies, the heritability estimate for the presence of ERP was h 2 = 0.49 (20).…”
Section: Introductionmentioning
confidence: 99%
“…Studies among first-degree relatives of patients with sudden arrhythmic death syndrome show that ERP is more prevalent in family members than in controls, indicating that ERP is an important potentially inheritable proarrhythmic trait (18,19). Moreover, in family studies, the heritability estimate for the presence of ERP was h 2 = 0.49 (20).…”
Section: Introductionmentioning
confidence: 99%
“…293 It is over-represented in families of UCA survivors 294 and autopsy negative SCD families. 295,296 There has not yet been a consensus curation for ERS. SCN5A variants with loss-of-function (determined by patch clamping expression studies) have been identified in 2-10% of patients with ERS, the patients showed signs of conduction slowing, supporting a depolarization phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that first-degree relatives of autopsy negative SCD victims have increased prevalence of ER with both rapidly ascending and horizontal/descending ST-segment morphologies, when compared to matched nuclear families [27]. A recent study demonstrated higher prevalence of ER in survivors of unexplained cardiac arrest (UCA) who had first-degree relatives with the ER pattern [28].…”
Section: St-segment Morphologymentioning
confidence: 99%